Synthesis Of A Shape-Changing Mechanism Using Computer-Aided Engineering - Mohd Zin, Adinda Hadirah (2020)
The research and development of shape-changing technologies continue to grow since it is predicted to revolutionize current technologies. Even today, shape-change technologies have been used in many applications, from large structures such as aircraft wings and to everyday use objects such as toys. Many studies were done on the shape-change materials, the objective is mainly to alter the microstructure of the material so it shape-change when targeted properties (temperature, pressure and etc.) change. Shape-change ability can also be obtained by manipulating the mechanisms. With shape-change technology, it is believed that the overall cost can be reduced then able to preserve the earth wellbeing. This project is to propose a shape-changing mechanism design in an aircraft wing by using actual wing profiles and shape-change coordinate from previous study and analyze the end transformation result. The data obtained is in form of coordinates, is then transferred into a CAD software which is Inventor to begin with CAD modelling and created a solid wing profile with 5 mm thickness and I 0 mm wide. From there, the shape-change mechanisms are designed for the CAD wing model. The design objective is to transform E420 wing shape to E850 wing shape. To hold the links together, a connector is designed as a new part. To realize it in an aircraft wing, two design approaches are proposed which are flexural hinges and revolute joints. The comparison of the two design approaches had shown that the flexural hinges suited the best for shape-change purposes, but it will require thorough studies on mathematics, thus, revolute joints design approach is selected for the transformation. It is suggested to do a proper research on flexural hinges especially in obtaining the correct diameter of sectioning. Next, the transformation had been done by manually adjusting the movement in model assemblies due to unsuccessful slider mating in Inventor software for tangential surface. It is suggested to do motion analysis using other software which is more advance in simulation. From the transformation, it was observed that the transformation from E420 to E850 is achievable but was not aligned accordingly to the 2D image canvas and has a total of 19 interferences equals to 6.59e-7 m3 volume. The transformation was then done separately between the upper and the lower part assemblies and both were able to transform accordingly. From this, it was identified that, the problem is due to the mismatching between the data used. Next, the wing weight is evaluated in its full wingspan of 1.74 m and 0.2 m chord. The weight calculated is 86.06 N for one wing. For a pair of revolute joints wing design, it only consumes 34% total weight of a 500 N UAV. Finally, the DOF calculated for this design is I , in which it can achieve the required positions with use of one actuator.